2004
DOI: 10.1016/j.nedt.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Nurses as information providers: facilitating understanding and communication of statistical information

Abstract: Nurses are increasingly being called upon to be the conveyers of important statistical information to patients. This trend is particularly evident in the domains of genetics and cancer screening. These new roles, however, demand new competencies, such as the ability to solve statistical problems, and the skill to communicate the answers effectively, as effective communication is an important ingredient in shared decision making. Genetic testing, perhaps more than other medical domains, relies heavily on the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A number of previous studies using the original Schwartz and Lipkus scales have shown a numeracy effect on understanding and decision making based on medical information (reviewed in [5,8-11]). Moreover, studies have been advancing for communicating quantitative risk information with consideration of patients’ numeracy, such as supplementing numerical data with visual or verbal aides, using natural frequencies rather than probabilities, or presenting risks with both negative and positive frames (reviewed in [10,11,40-43]). Considering our results and these earlier findings, such care would be called for when communicating medical information to those with low numeracy in Japan, and possibly in other countries where general math performance is deemed to be high.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies using the original Schwartz and Lipkus scales have shown a numeracy effect on understanding and decision making based on medical information (reviewed in [5,8-11]). Moreover, studies have been advancing for communicating quantitative risk information with consideration of patients’ numeracy, such as supplementing numerical data with visual or verbal aides, using natural frequencies rather than probabilities, or presenting risks with both negative and positive frames (reviewed in [10,11,40-43]). Considering our results and these earlier findings, such care would be called for when communicating medical information to those with low numeracy in Japan, and possibly in other countries where general math performance is deemed to be high.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some authors 6 recommend teaching undergraduate students about the most commonly used statistics found in the nursing literature. Despite these recommendations, many RNs continue to lack competency in statistical analysis interpretation as they enter into practice, 7,8,9 and this need for proficiency carries forward as RNs enter graduate nursing programs. Consequently, Beitz 7 recommends the use of a heuristic device to help nurses identify the statistical test to be used to answer research questions in the context of the research design.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Similarly, researchers should avoid complex statistical modeling that impedes clinicians' understanding of the health-related QOL data. 22,23 Frequencies, 23 change in scores over time, and numbers of patients reporting clinically meaningful changes in scores should also be reported. 22…”
Section: Communication Of Qol Data To Patients For Their Usementioning
confidence: 99%